Fertilize of Peat Soil with Phosphat Fertilizer in Different Grade Based on Parameter of Physical Chemistry - Vina Damayanti; Saberina Hasibuan; Syafriadiman ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted from February-April 2015 in the Laboratory Aquaculture Environmental Quality, Faculty of Fisheries and Marine Sciences University of Riau Pekanbaru. The method used in this study is an experimental method using a Complete Random Design (CRD) with 1 factor, 5 treatments and 3 replications. The treatment used in this experiment is P0:Without application of fertilizer (control), P1:grade N-P-K (20-10-0), P2:grade N-P-K (20-20-0), P3:grade N-P-K (20-30-0) and P4:grade N-P-K (20-40-0). Result showed that the given of phosphat fertilizer with different grade effected to some soil parameter quality. For parameter pH and P-available soil the best treatments is grade N-P-K:20-40-0 (P4). For N-total and C/N ratio the best treatment is grade N-P-K:20-10-0 (P1). For soil organic matter content the best treatment is control (P0). For the parameters of color, texture, bulk density and cation exchange capacity of phosphorus fertilizer with different grade is no effected. Results of measurements of water quality parameters during research that ranged is for pH of water from 3,75 to 6,27 and temperature of water that range from 27-310C. The range of water pH and temperature is still quite good for aquatic organisms .Keyword : phosphat fertilizer, peat soil, soil physical chemistry parameter